Elevated microRNA-520g in pre-eclampsia inhibits migration and invasion of trophoblasts. (March 2017) - Jiang, Liansheng; Long, Anxiong; Tan, Longyi; Hong, Mao; Wu, Jingjing; Cai, Leiming; Li, Qian
Abstract: Introduction: Pre-eclampsia (PE) is a common and severe obstetric complication. MicroRNAs (miRs) have emerged as molecules that are associated with the disease. Methods: Quantitative reverse transcription PCR (RT-qPCR) was used for serum miR-520g characterization from 19 severe pre-eclamptic and 19 normal pregnancies. In situ hybridation was adopted to localize microRNA-520g (miR-520g). Migration and invasion of HTR-8/SVneo cells were evaluated after miR-520g mimic treatment with transwell system. MiR-520g target gene was verified in luciferase reporter system. Results: The expression of serum miR-520g displayed an upward trend as pregnancies progress. At first-trimester, miR-520g in pre-eclampsia was significantly higher than that in the control, but no significant differences were found in the second and last trimesters. MiR-520g localized in cytoplasm of early trimester placental trophoblasts. The migration and invasion of HTR8/SVneo were inhibited by miR-520g mimic treatment. Matrix metalloproteinase 2 (MMP2) was verified as a direct target of miR-520g. Conclusions: Elevated maternal serum level of miR-520g level in first trimester was detected in patients with severe PE. By suppressing the migration and invasion of trophoblast via at least partial inhibition of MMP2 translation inhibition, miR-520g might play a role in the defective spiral artery remodeling, and thus contribute to pre-eclampsia pathophysiology. Highlights: The expression of serum miR-520 g displayed an upward trend as pregnancies progress. Elevated maternal serum level of miR-520 g level in first trimester was detected in patients with severe PE. MiR-520 g localized in cytoplasm of early trimester placental trophoblasts. The migration and invasion of HTR8/SVneo were inhibited by miR-520 g mimic treatment. Matrix metalloproteinase 2 (MMP2) was verified as a direct target of miR-520 g.